Anxiolytic and antidepressant like effects of Zamzam water in STZ-induced diabetic rats, targeting oxidative stress, neuroinflammation, BDNF/ERK/CREP pathway with modulation of hypothalamo-pituitary–adrenal axis - Taha, Medhat; Mahmoud, Mohamed Ezzat; Al-Kushi, Abdullah G.; Sarhan, Anas; Abdelbagi, Omer; Baokbah, Tourki A. S.; Babateen, Omar; El-Shenbaby, Ibrahim; Qusty, Naeem F.; Elazab, Sara T. (Frontiers in Neuroscience, 2023)
Introduction: Recent studies have reported a strong relationship between diabetes and anxiety-and depression-like behaviors; however, there is a lack of information on the underlying pathophysiology.Alkaline Zamzam water (ZW), which is rich in several trace elements, has neuroprotective properties.2 This is a provisional file, not the final typeset article.This study aimed to investigate the anxiolytic and antidepressant effects of ZW against diabetesinduced behavioral changes and shed light on the possible underlying mechanisms.Methods: Forty-eight rats were divided into four experimental groups (n = 12): group I (control group), group II (Zamzam water group), group III (diabetic group), and group IV (diabetic + Zamzam water group). Diabetes was induced by an intraperitoneal injection of 60 mg/kg streptozotocin (STZ). At the end of the experiment, the forced swimming test (FST) was used to assess depression-like effects. The elevated plus maze test (EPMT) and open field test (OFT) were performed to evaluate anxiety-like behavior. Blood levels of the hypothalamic-pituitary-adrenal (HPA) axis were measured, and prefrontal cortex and hippocampal tissue samples were removed for histological, immunohistochemical, ELISA, and Q-PCR analyses. Results: ZW significantly decreased the immobility time in the FST, indicating an antidepressant effect (p < 0.001). Additionally, ZW significantly improved the OFT and open field entry (OFE) percentages in the EPMT, increasing center crossing and decreasing grooming and fecal boli in the OFT. This indicated an anxiolytic-like effect in diabetic rats with histological improvement. Interestingly, ZW significantly increased prefrontal cortical and hippocampal levels of antioxidant enzymes and the Nrf2/HO-1 pathway. It also modulated the HPA axis by increasing cortisol and corticotropin-releasing hormone (CRH) levels, with a decrease in ACTH and an increase in monoamine neurotransmitters. Furthermore, diabetic rats that received ZW showed a decrease in the inflammatory markers TNF-α and GFAP by immunohistochemistry and in the mRNA levels of NFκB, IL-1β, and IL6. In addition, ZW downregulated the expression of the BDNF/ERK2/CREP pathway. Conclusions: Our results suggested a neuroprotective effect of ZW against diabetes-induced anxiety-and depression-like behaviors and explored the underlying mechanisms. These findings suggest a promising therapeutic strategy for patients with diabetes who experience anxiety and depression.